2020
DOI: 10.21203/rs.3.rs-69386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global expression of noncoding RNome reveals dysregulation of small RNAs in patients with HTLV-1–associated adult T-cell leukemia: a pilot study

Abstract: Background Adult T cell lymphoma/leukemia (ATLL) is a peripheral T-cell neoplasm caused by human T-cell lymphotropic virus-1 (HTLV-1). Small RNAs (sRNAs), including microRNAs (miRNAs), play a pivotal role in the initiation and development of hematological malignancies and may represent potential therapeutic target molecules. However, little is known about how these molecules impact on the pathogenesis of ATLL. In this study, we aimed to identify sRNA expression signatures associated with ATLL and to investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…To date, HTLV-I-infected cell lines have been studied using microarray and PCR-based approaches to identify and characterize cellular miRNAs [18]. Our group recently revealed distinct sRNA signatures for ATLL and proposed that these signatures could be employed as biomarkers to detect ATLL at an early stage [19]. Furthermore, in patients with active ATLL, we observed that miR-451-3p was the miRNA that was most significantly downregulated, suggesting that this miR could be a promising therapeutic target in ATLL via the AMPK/Notch signaling pathway.…”
Section: Molecular Studies Have Shown That Viral Proteins Disrupt Bio...mentioning
confidence: 99%
“…To date, HTLV-I-infected cell lines have been studied using microarray and PCR-based approaches to identify and characterize cellular miRNAs [18]. Our group recently revealed distinct sRNA signatures for ATLL and proposed that these signatures could be employed as biomarkers to detect ATLL at an early stage [19]. Furthermore, in patients with active ATLL, we observed that miR-451-3p was the miRNA that was most significantly downregulated, suggesting that this miR could be a promising therapeutic target in ATLL via the AMPK/Notch signaling pathway.…”
Section: Molecular Studies Have Shown That Viral Proteins Disrupt Bio...mentioning
confidence: 99%